2009
DOI: 10.1161/circulationaha.108.813303
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Prolyl Hydroxylase Domain Proteins Promotes Therapeutic Revascularization

Abstract: Background-The hypoxia-inducible transcription factor (HIF) subunits are destabilized via the O 2 -dependent prolyl hydroxylase domain proteins (PHD1, PHD2, and PHD3). We investigated whether inhibition of PHDs via upregulating HIF might promote postischemic neovascularization. Methods and Results-Mice with right femoral artery ligation were treated, by in vivo electrotransfer, with plasmids encoding for an irrelevant short hairpin RNA (shRNA) (shCON [control]) or specific shRNAs directed against HIF-1␣ (shHIF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
74
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(76 citation statements)
references
References 44 publications
2
74
0
Order By: Relevance
“…In line with our results, a recent report showed that downregulation of PHD2 by shRNA enhanced neoangiogenesis in a mouse model of myocardial infarction (Huang et al, 2008). A different study evaluated the effects of shPHD1, shPHD2, and shPHD3 on neovascularization in a mouse hindlimb ischemia model (Loinard et al, 2009). Electroporation of plasmid vectors was used and silencing of PHDs triggered postischemic neovascularization, with shPHD2 and shPHD3 having the most robust effects.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In line with our results, a recent report showed that downregulation of PHD2 by shRNA enhanced neoangiogenesis in a mouse model of myocardial infarction (Huang et al, 2008). A different study evaluated the effects of shPHD1, shPHD2, and shPHD3 on neovascularization in a mouse hindlimb ischemia model (Loinard et al, 2009). Electroporation of plasmid vectors was used and silencing of PHDs triggered postischemic neovascularization, with shPHD2 and shPHD3 having the most robust effects.…”
Section: Discussionsupporting
confidence: 87%
“…Inhibition of HIF-1-alpha degradation through short hairpin RNA (shRNA) knockdown of PHD2 has been shown to significantly improve neovascularization, which in turn improved cardiac function in a mouse model of myocardial infarction (Huang et al, 2008). Moreover, inhibition of PHD by shRNA provides a promising proangiogenic therapeutic approach, as in vivo electrotransfer of plasmids with either shPHD2 or shPHD3 has been shown to significantly improve postischemic neovascularization in a mouse model of PAD (Loinard et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesized that these variations, which are linked to Prakriti groups that are differently predisposed to diseases, may lead us to identification of predictive markers for differential responsiveness to disease and environment. As a proof of concept, we studied EGLN1 because it plays a key role in oxygen homeostasis and is also believed to be a target of many pharmacological interventions that aim to stabilize HIF or lower HIF activity (9)(10)(11). Although variations in genes of pathways related to hypoxia, such as HIF-1, endothelial function, and vascular remodeling, have been studied (12)(13)(14)(15)(16)(17), none of the studies so far have reported polymorphisms linked to EGLN1 in high-altitude adaptation.…”
Section: Discussionmentioning
confidence: 99%
“…This complexity reflects not only the crucial role of HIF1 in maintaining oxygen homeostasis but also the need to safeguard against its inappropriate activation. Previous reports have linked the PHD3-HIF and SUMOylation pathways with pathologies such as cancer and ischemia (Cheng et al, 2006;Chen et al, 2011;Flotho and Melchior, 2013;Fox et al, 2011;Loinard et al, 2009;Mo et al, 2005;Silveirinha et al, 2013;Su et al, 2010;Wang and Banerjee, 2004;Xue et al, 2010). In light of these findings, there is a great interest in the development of drugs targeting these pathways.…”
Section: Discussionmentioning
confidence: 99%